Low Muscularity and Myosteatosis Is Related to the Host Systemic Inflammatory Response in Patients Undergoing Surgery for Colorectal Cancer. Issue 2 (February 2016) - Malietzis, George; Johns, Neil; Al-Hassi, Hafid O.; Knight, Stella C.; Kennedy, Robin H.; Fearon, Kenneth C. H.; Aziz, Omer; Jenkins, John T.
Abstract : Objective: We examined the relationships between computed tomography (CT)–defined skeletal muscle parameters and the systemic inflammatory response (SIR) in patients with operable primary colorectal cancer (CRC). Background: Muscle depletion is characterized by a reduced muscle mass (myopenia) and increased infiltration by inter- and intramuscular fat (myosteatosis). It is recognized as a poor prognostic indicator in patients with cancer, but the underlying factors remain unclear. Methods: A total of 763 patients diagnosed with CRC undergoing elective surgical resection between 2006 and 2013 were included. Image analysis of CT scans was used to calculate Lumbar skeletal muscle index (LSMI), and mean muscle attenuation (MA). The SIR was quantified by the preoperative neutrophil to lymphocyte ratio (NLR) and albumin levels. Correlation and multivariate regression analysis was performed to identify independent relationships between patient SIR and muscle characteristics. Results: Patients with NLR > 3 had significantly lower LSMI and lower MA than those with NLR < 3 [LSMI = 42.07 cm 2 m −2 vs 44.27 cm 2 m −2 ( P = 0.002) and MA = 30.04 Hounsfield unit (HU) vs 28.36 HU ( P = 0.016)]. Multivariate logistic regression analysis showed that high NLR [odds ratio (OR) = 1.78 (95% confidence interval [CI]: 1.29–2.45), P < 0.001] and low albumin [OR = 1.80 (95% CI: 1.17–2.74), P = 0.007] were independent predictors of reduced muscle mass. High NLR was significantly related with a low mean MA and hence myosteatosis [OR = 1.60 (95% CI: 1.03–2.49), P = 0.038]. Conclusions: These results highlight a direct association between myopenia, myosteatosis, and the host SIR in patients with operable CRC. A better understanding of factors that regulate muscle changes such as myopenia and myosteatosis may lead to the development of novel therapies that influence a more metabolically "healthy" skeletal muscle and potentially alter cancer outcomes.